Lenalidomide as a novel therapy for gastrointestinal angiodysplasia in von Willebrand disease. Issue 2 (15th February 2018) - Khatri, N. V.; Patel, B.; Kohli, D. R.; Solomon, S. S.; Bull‐Henry, K.; Kessler, C. M.
Abstract : Introduction: Lenalidomide is a thalidomide analog with anti‐angiogenic properties. Previous case reports suggest its efficacy in preventing gastrointestinal bleeding (GIB) secondary to angiodysplasia (AD) in hereditary haemorrhagic telangiectasia and potentially in reversing AD. We present the first case series to explore lenalidomide as a treatment for AD‐related GIB in patients with von Willebrand disease (VWD). Methods: A retrospective chart review was conducted to include patients with VWD, who were evaluated from 2010 to 2013 and who had received lenalidomide to treat recurrent GIB secondary to AD. All patients had failed single‐agent use of antifibrinolytic agents. Patients were observed for at least 2 years on therapy. Results: Five patients (3 males; 68.2 ± 4.9 years) with VWD (3 with type 3 and 1 each with types 1 and 2a) and AD were found. Sites of AD included the stomach, duodenum, jejunum and colon. Lenalidomide was started at 5 mg oral daily. Uptitration to 10 and 15 mg in 1 patient each was necessary due to recurrence of GIB. The mean number of endoscopies performed for control of GIB post lenalidomide was significantly lower compared to pretherapy (0.25 vs 5.50; P  = .001). Mean bleed‐free duration on lenalidomide was 12.6 ± 4.7 months. Three patients have reported no GIB on lenalidomide. Conclusion: This case series demonstrates significantly reduced number of endoscopies and increased bleed‐free duration with lenalidomide treatment in selected patients with VWD and recurrent GIB from AD. Prospective multicenter trials are needed to further define the role of lenalidomide in the management of GIB from angiodysplasia and VWD.